The determinants of apprenticeship training with particular reference tobusiness expectations - Hans Dietrich; Hans-Dieter Gerner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2007)
Whilst in applied empirical research, training in general human capital is mainly explained by structural characteristics of firms, this paper introduces business expectations as an additional explanatory factor. Business expectations are strictly time-variate and firm-specific and reflect both a firm's development in competitive markets and in the business cycle. We assume that a firm's business expectations strongly modify the cost-utility concept for firms' decisions as regards providing apprenticeship places. When controlling for firms' structural characteristics, static econometric models support our assumption that a change in business expectations leads to an asymmetric adjustment process of firms' qualitative decisions regarding apprenticeship training. Concerning the quantitative decision as to how many apprenticeship places a firm provides we found a significant but not asymmetric response to a change in business expectations. A dynamic approach confirms the results obtained in the static models of a symmetric quantitative adjustment process in a short-term perspective. In a longer perspective the dynamic model supports the assumption of an asymmetric quantitative adjustment process. Further on an application shows that an increasing uncertainty regarding business expectations tends to reduce the apprenticeship training at firm level.
Keywords: 330; Ausbildungsverhalten - Determinanten; Betrieb; Ausbildungsbetrieb; Unternehmensentwicklung; Personalpolitik; Kosten-Nutzen-Analyse; Ausbildungskosten; betriebliche Berufsausbildung - Nutzen; betriebliche Berufsausbildung; Bildungsökonomie; Bildungsinvestitionen; wirtschaftliche Situation